Readiness of SMEs on Digital Payment for Business Sustainbility - Novitasari Agus Saputri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
This study aims to analyze the readiness of MSMEs in using digital payments to support business sustainability in terms of the level of risks and benefits of using digital payments, the facilities they have, the ability to use digital payments and the needs of MSMEs for digital payments along with the development of current technology. The data analysis technique used was descriptive qualitative data analysis technique with the stages of data analysis, namely the data documentation stage, data reduction, data display and drawing conclusions. The results of this study indicate that in general the respondents, namely MSME business actors, strongly agree to use e-money in carrying out company operations. The use of e-m money is considered effective to support the company's operational activities. Apart from that, the use of e-money provides overall usefulness. The use of e-money is likely to pose risks to its users, both time and cost risks. In addition to the risks to be faced, respondents have the assumption that the use of e-money will also face losses. The losses are not proportional to the benefits to be received in the future. This is reinforced by previous research which stated that several factors that influence someone to adopt technology in the form of using electronic money are security and confidentiality, usability benefits, user convenience, fun, trust and risk. Meanwhile, the use of digital payments is considered capable of supporting business sustainability.